Learning Outcomes of Post-Pandemic Invertebrate Systematics Practicum for Biology Education Students - Saskia, Dinda Putri; Kusumadani, Annur Indra (Journal of Biology Learning, 2023)
The covid-19 pandemic has an impact on student learning outcomes in the practicum of the invertebrate systematics course.The aim of this research is to determine the learning outcomes of post-pandemic invertebrate systematics practicum for students in semester 5, academic year 2022/2023. The method used in this research is a descriptive qualitative method. The sample used in this research was 5th semester students with a total of 5 classes totaling 97 students. The sampling technique used was the Population Sampling Technique. Data was obtained from a list of TKP scores, report scores, response scores and student perceptions submitted using a Google Form questionnaire. The results obtained by Biology Education students in the Invertebrate Systematics Practicum were based on TKP scores of 45.4% in the high category, 49.5% medium and 5.2% low. Based on the report value, 96.9% is in the high category, 2.0% is medium and 1.0% is low. Based on the response value, 3.1% were in the high category, 28.9% were medium and 68.0% were low. And based on the results of the student perception questionnaire, it can be interpreted that post-pandemic learning has had a positive impact, including being able to carry out practicums in the laboratory and improving student learning outcomes.